Photothermal Therapy for the Treatment of Glioblastoma: Potential and Preclinical Challenges - Bastiancich, Chiara; Da Silva, Anabela; Estève, Marie-Anne (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is a very aggressive primary malignant brain tumor and finding effective therapies is a pharmaceutical challenge and an unmet medical need. Photothermal therapy may be a promising strategy for the treatment of GBM, as it allows the destruction of the tumor using heat as a non-chemical treatment for disease bypassing the GBM heterogeneity limitations, conventional drug resistance mechanisms and side effects on peripheral healthy tissues. However, its development is hampered by the distinctive features of this tumor. Photoabsorbing agents such as nanoparticles need to reach the tumor site at therapeutic concentrations, crossing the blood brain barrier upon systemic administration. Subsequently, a near infrared light irradiating the head must cross multiple barriers to reach the tumor site without causing any local damage. Its power intensity needs to be within the safety limit and its penetration depth should be sufficient to induce deep and localized hyperthermia and achieve tumor destruction. To properly monitor the therapy, imaging techniques that can accurately measure the increase in temperature within the brain must be used. In this review, we report and discuss recent advances in nanoparticle-mediated plasmonic photothermal therapy for GBM treatment and discuss the preclinical challenges commonly faced by researchers to develop and test such systems.